(untitled) - Leon, Steven J. (Upper Saddle River, N.J., 1998)
Renowned for its thoroughness and accessibility, this best-selling text by one of the leading figures in linear algebra reform offers students a challenging yet enjoyable study of linear algebra that is infused with an abundance of applications. Balancing coverage of mathematical theory and applied topics, it takes extra care in explaining concepts clearly so that students at a variety of levels can read and understand the material. Numerous worked examples are integrated throughout the text. This revision stresses the important roles played by geometry and visualization in linear algebra. ATLAST Computer Exercises for Linear Algebra a project manual using MATLAB--may be packaged free with the text.
Keywords: Algebras, Linear,Đại số tuyến tính